Interface and bulk engineering of VO2 thin film deposited on Si for multi-level metal-to-insulator transitions - Choi, Hyobin; Lee, Wanggon; Lim, Jaeseong; Shin, Heecheol; Kumar, Mohit; Seo, Hyungtak (Applied Surface Science, 2023)
Vanadium dioxide (VO2), as a representative metal-to-insulator transition (MIT) material, is of utmost interest for various device applications such as memory devices, memristors, Mott transistors, and temperature sensors due to its MIT temperature near room temperature. However, it is difficult to fabricate a stable VO2 film, especially on Si wafer since its interfacial mixing alters the physicochemical properties of VO2. This study demonstrates that stable VO2 thin films with reduced interfacial mixing can be fabricated using a sequential process consisting of a vanadium metal e-beam evaporator and thermal post oxidation. The device fabricated with VO2 shows distinctive multi-level MIT characteristics with bulk current–voltage curves with reproducible on/off switching behavior, which matches well with nanoscale transition probed by the conductive atomic force microscopy analysis. Our findings pave the way to produce highly stable VO2 thin films as well as applications for integrated Si-based semiconductor devices such as memory devices, ultrafast switches, and others.
Keywords: Device application; Interfacial mixing; Memristor; Metal-to-insulator transition; Metal-to-insulator transitions; Multilevels; Nano scale; Near room temperature; Transition materials; VO 2 thin films; Interfacial mixing; Metal-to-Insulator Transition (MIT); Nanoscale; VO2 thin film